2011
DOI: 10.7150/ijms.8.210
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Oxaliplatin-Induced Hypersensitivity Reactions in Japanese Patients with Advanced Colorectal Cancer

Abstract: Objective: Previously, we suggested that oxaliplatin (L-OHP)-related grade 3/4 hypersensitivity reactions occurred immediately after the initiation, but grade 1/2 reactions did not. This study was conducted to clarify the risk factors for L-OHP-related hypersensitivity reactions.Methods: Clinical data from 108 Japanese patients with colorectal cancer were analyzed, who were treated with L-OHP-containing regimens, FOLFOX4 and/or mFOLFOX6. The risk factors examined included demographic data, preexisting allergie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 32 publications
1
36
2
Order By: Relevance
“…As previously described, age and female gender were identified as risk factors [7,9,13]. Interestingly, we showed that 94% of hypersensitive patients were women, finding which was not reported yet.…”
Section: Discussionsupporting
confidence: 48%
“…As previously described, age and female gender were identified as risk factors [7,9,13]. Interestingly, we showed that 94% of hypersensitive patients were women, finding which was not reported yet.…”
Section: Discussionsupporting
confidence: 48%
“…In a large Phase III clinical trial (MOSAIC) of oxaliplatin, allergic reactions were present only in 10.6% of the patients, and severe toxicity (grade III/IV) was present in 2.9% of them [14]. More recent data, however, present an HSR incidence ranging from 8.9 to 23.8% (Table 1) [10,[15][16][17][18][19][20][21], whereas severe anaphylactic reactions are present in a proportion < 2% [13,[22][23][24]. Shao et al [10] reported an incidence of 12.7% with a median of 10 infusions and the median time of onset from the start of infusion was 40 min.…”
Section: Incidencementioning
confidence: 84%
“…The authors suggested that the association between HSRs and younger age and female gender could be attributed to a potential role of hormonal influences. In another study by Seki et al [16], a higher neutrophil count and a lower monocyte count were reported to be risk factors for grade III/IV HSRs in Japanese patients.…”
Section: Risk Factorsmentioning
confidence: 96%
See 1 more Smart Citation
“…Most reported cases of chemotherapy-induced HSRs are either immediate and IgE-mediated (type I), or delayed and T-cell mediated (type IV), according to the Gell and Coombs classification [3][4][5][6][7][8][9] . In our daily oncological practice, these HSRs mainly involve platinum and taxane, and clinical manifestations range in severity from pruritus to anaphylactic shock.…”
mentioning
confidence: 99%